2007
DOI: 10.1007/s10389-007-0129-x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational risk factors for work-related disorders in greenhouse workers

Abstract: Aim This study reviews the evidence on the association between working in greenhouses and the occurrence of muscelosckeletal, reproductive and respiratory disorders, dermal effects, cancer and neurobehavioral effects. Subjects and methods PUBMED, MEDLINE and EBSCO literature bases were searched to identify epidemiological studies conducted over 1996-2006 that focused on the health outcomes of greenhouse workers. Three exclusion criteria were used to limit the selection to studies with quantitative assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 46 publications
(65 reference statements)
0
4
0
1
Order By: Relevance
“…The main hazards of working in greenhouses include: injury from materials, problems related to working position, chemicals including pesticides, endotoxins, dusts, and work at height [410]. Dermatitis, musculoskeletal complaints, respiratory system diseases, and neurological diseases are the most common diseases among greenhouse workers [11]. However, the number of studies on health and safety issues of greenhouse workers is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The main hazards of working in greenhouses include: injury from materials, problems related to working position, chemicals including pesticides, endotoxins, dusts, and work at height [410]. Dermatitis, musculoskeletal complaints, respiratory system diseases, and neurological diseases are the most common diseases among greenhouse workers [11]. However, the number of studies on health and safety issues of greenhouse workers is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Some farmers (31%, n = 52) revealed that their internal clothes have the same odor of pesticide solution at the end of working day. We found about 11 insecticides are commonly used in greenhouses for insects, nematodes and mites control, with application rates ranged from 1 -2.5 kg/ha ( [34] who reviewed the evidence on the association between working in greenhouses and the occurrence of and respiratory disorders and indicated that greenhouse exposure is associated with an increased risk of respiratory disorders, sensitization to allergens and skin reactions. Further supports to our hypothesis come from the work of Liu et al [33] who evaluated the prevalence of farmer's lung disease (FLD) and revealed that prevalence of FLD among these farmers was 5.7% (308/5420) and the risk factors for FLD were years of age, shorter time interval for re-entry greenhouse, ventilation frequency of greenhouse.…”
Section: Risk Factors Emerged From Pesticide Applicationmentioning
confidence: 99%
“…They revealed that prevalence of FLD among these farmers was 5.7% (308/5,420) and the risk factors for FLD were years of age, shorter time interval for re-entry greenhouse, ventilation frequency of greenhouse. Earlier, Jurewicz et al [34] reviewed the evidence on the association between working in greenhouses and the occurrence of and respiratory disorders. They indicated that greenhouse exposure was associated with an increased risk of respiratory disorders, sensitization to allergens and skin reactions.…”
Section: Introductionmentioning
confidence: 99%
“…A number of groups have reviewed the association between the exposure to specific chemicals or groups of chemicals and TTP, and support the notion that environmental exposure may be hazardous for human fertility (Sallmen, 2001;Jensen et al, 2006;Jurewicz et al, 2007). However, these reviews all focused on the effects, mainly in males, of exposure to a specific chemical or a group of chemicals on fertility or reproductive function rather than focusing on the broader spectrum of chemical exposures and their effects on TTP in both men and women.…”
Section: Conceptionmentioning
confidence: 96%